2010
DOI: 10.1177/0891988710373596
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic Symptoms in a Population-Based Sample of 85-Year-Old Individuals With Dementia

Abstract: Psychotic symptoms are common in elderly persons with dementia. These symptoms affect a person's ability to function in daily life and put strain on the caregiver. Most studies focus on psychotic symptoms in clinical samples with Alzheimer disease (AD). Thus, their prevalence and relation with dementia subtype and severity in very old populations is unclear. We assessed a representative sample of 85-year-old individuals living in Gothenburg, Sweden (n = 494) using neuropsychiatric examinations, key informant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Unfortunately, despite a useful longitudinal approach, psychosis was not described in terms of its components, limiting the utility of this study in contributing to the understanding of the neurobiology of delusions. Very recently, in a cross-sectional sample of much older adults with AD (>85 years of age), Ostling and colleagues [15] reported that 22% had delusions and 30% had hallucinations. Although psychosis in general and hallucinations increased with dementia severity, no statistically significant association was found between delusions and dementia severity.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Unfortunately, despite a useful longitudinal approach, psychosis was not described in terms of its components, limiting the utility of this study in contributing to the understanding of the neurobiology of delusions. Very recently, in a cross-sectional sample of much older adults with AD (>85 years of age), Ostling and colleagues [15] reported that 22% had delusions and 30% had hallucinations. Although psychosis in general and hallucinations increased with dementia severity, no statistically significant association was found between delusions and dementia severity.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…On the contrary, BG's dementia was characterized by severe and multiple cognitive impairments, suggesting diffuse cortical damage (i.e., retrograde and autobiographical amnesia, aphasia, constructional and dressing apraxia, a complex misidentification syndrome, etc.). Second, hallucinations in the early stages of subcortical vascular dementia do not usually involve symptoms that occur during sleep induction or awakening, such as the preferential hypnagogic and hypnopompic hallucinations experienced by BG [65]. Third, the clinical picture of subcortical vascular dementia involves widespread manifestations, including cognitive impairments, personality and mood disorders (i.e., apathy, irritability, and vascular depression), psychotic symptoms, gait disturbances, motor dysfunction, and urinary symptoms [67, 69].…”
Section: Discussionmentioning
confidence: 99%
“…32 It is also worth noting that psychotic symptoms appear to be more common among inpatient populations than outpatient populations, 10 and that dementia severity appears to be positively associated with the presence and severity of psychosis. 33,34 Psychosis in Alzheimer's disease typically has a unique clinical appearance in comparison to psychosis in other late-life, non-dementia illnesses. For instance, unlike in schizophrenia, the hallucinations seen in Alzheimer's disease tend to be visual, not auditory, in nature, 10 and the delusions tend not to be bizarre or complex, but are simple/non-complex.…”
Section: Alzheimer's Disease and Other Dementiasmentioning
confidence: 98%
“…34 In vascular dementia, as in Parkinson's dementia, but not Alzheimer's or Lewy body dementia, the severity of dementia does not appear to be associated with the presence or severity of psychosis. 33,34 Secondary Psychoses In addition to the aforementioned neuropsychiatric disorders, a variety of medical and neurological problems in older individuals can result in psychosis. It is important to identify such cases since the management of symptoms depends on the underlying cause and will tend to focus on addressing the primary problem.…”
Section: Alzheimer's Disease and Other Dementiasmentioning
confidence: 99%